KEANEKARAGAMAN TUMBUHAN HUTAN "GUNUNG LUMUT" KABUPATEN PASIR, KALIMANTAN TIMUR - Wiriadinata, Harry (BERITA BIOLOGI, 2008)
The diversity of forest plants found in three locations in Gunung Lumut Protected Forest, East Kalimantan had been studied in November 2005 in which 252 number of herbarium specimen have been collected, encompassing 194 of herbs and shrubs,33 of trees, 21 numbers of climbers and 4 numbers of orchids.Among the collections like some members of Begoniaceae are interesting for their limited distribution and endemicity.